Latihan aerobik dengan senam intensitas rendah terhadap kebugaran fisik dan indeks massa tubuh pada lansia - Liskustyawati, Hanik; Santoso Sabarini, Sri (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
Decreased physical activity in the elderly is a problem today, lack of physical activity and not understanding physical activity causes a decrease in fitness and body mass index for the elderly. This study aims to improve the physical fitness and body mass index of the elderly with Aerobic exercise with low-intensity gymnastics. This study was a quasi-experiment with a single-group pretest posttest group design. Subjects involved with purposive sampling techniques with sample criteria with the application of inclusion and exclusion criteria with 40 elderly social services in Surakarta city. Instruments to measure physical fitness used the Rock Port test as far as 1609 m and body mass index measurements of weight and height. Data analysis using prerequisite tests and Kolmogorov Smirnov tests with SPPS 25 for Windows programs. The homogeneity test in this study used Test F. The data obtained were processed using IBM SPSS version 25 and paired T-test. The results showed a significant difference between physical fitness before and after aerobic exercise with low-intensity gymnastics, it was from the results of significance 0.056 (<0.05). While the results showed there was a significant difference between body mass index before and after aerobic exercise with low-intensity gymnastics from the results of significance P = 0.028 (<0.05). From these results, aerobic exercise can improve physical fitness and body mass index in the elderly. So that the elderly can take advantage of these activities to maintain their body health.